Hardware Design of Non-contact Voltage Detector Based on STM32 Microcontroller. Issue 6 (March 2020) - Zhang, Xuemin; Zhang, Peng; Shi, Yuqing; Dang, Junpeng; Yuan, Liwei
Abstract: In view of the time-consuming and labor-intensive problems of traditional contact electroscopes, this paper designs a hardware system of non-contact voltage detector based on STM32 single-chip microcomputer. The hardware design mainly includes signal amplification and conditioning circuit and power module, Wireless transceiver module, display and alarm module, etc. In order to reduce the distortion of electric field caused by human during measurement, a wireless transceiver module device is adopted, which has a simple structure and can meet the engineering requirements of the non-contact power inspection of the transmission line.